Analisis Kebijakan Tarif maupun Non tarif Amerika Serikat terhadap Tiongkok dalam Perang Dagang - Cahyani, Risya Amanda; Putranti, Ika Riswanti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
This research seeks to find out the ambition behind the United States's aggressiveness towards China by providing tariff and non-tariff policy to cause a trade war. This research is qualitative research, because it seeks to explain the reasons possessed by the United States in order to provide tariff and non tariff barriers to China. The time span used for this research is from December 2017 to September 2019. This research uses library research for data collection through books, journals, and search engines. The data analysis technique used in this paper is congruent analysis. After going through the research process, the researcher found the answer that the United States wanted to gain hegemony over China by providing tariff and non-tariff policies that caused trade war